Women's micro-narratives of the process of abortion decision-making : justifying the decision to have an abortion - Mavuso, Jabulile Mary-Jane Jace (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
Much of the research on abortion is concerned with determining women's psychological outcomes post-abortion. There is a small, but increasing, body of research around women's experiences of abortion (conducted predominantly in Scandinavian countries where abortion laws are liberal). However, research around the decision-making process regarding abortion, particularly research that locates the decision to have an abortion within the economic, religious, social, political, and cultural aspects of women's lives and that looks at women's narratives, is virtually non-existent. Drawing on Foucauldian and feminist post-structuralism as well as a narrative-discursive approach, this study sought to explore women's micro-narratives of the abortion decision-making process in terms of the discourses used to construct these micro-narratives and the subject positions made available within these discourses. This study also sought to determine whether the power relations referred to by participants contributed to unsupported and unsupportable pregnancies and the implications this had for reproductive justice. Purposive sampling was used to recruit a total of 25 participants from three different abortion facilities in the Eastern Cape. Participants were 'Black' women, mostly unemployed and unmarried with ages ranging between 19 and 35 years old. In analysing and interpreting participants' narratives, the picture that emerged was an over-arching narrative in which women described the abortion decision as something that they were 'forced' into by their circumstances. To construct this narrative, women justified the decision to have an abortion by drawing on discourses that normalise certain practices located within the husband-wife and parent-child axes and make the pregnancy a problematic, unsupported and unsupportable one. Gendered and generational power relations reinforced this and contributed to the denial of reproductive justice
Keywords: Abortion -- Psychological aspects; Pregnancy, Unwanted -- Psychological aspects; Narrative therapy; Post-abortion syndrome